Pengaruh Permainan Air Akuatik (Aquatic) Terhadap Kemampuan Berpikir Kritis Anak Usia 5-6 Tahun - Metalia Tantu; Nunung Suryana Jamin; Waode Eti Hardiyanti (Student Journal of Early Childhood Education, 2025)
This study focuses on answering the question of whether there is an influence of aquatic water games on the critical thinking skills of children aged 5-6 years in one of the kindergarten schools (TK) in Pohuwato Regency. The research method used is quantitative pre-experimental experiment (on-group pretest-posttest design). The sample in this study was 15 children in class B. The results of the study showed that the average pre-test value was 19.06 with a standard deviation of 3.5550 and the average post-test value was 35.06 with a standard deviation of 1.3870. These results prove that there is a significant influence before and after treatment. Based on the hypothesis testing that has been carried out through the t-test, it shows that the sig. (2-tailed) value is obtained, namely the t-count value of 20.6559 and the t-table value at the 0.05 real level is 2.145. So t-count> t-table then H0 is rejected or H1 is accepted. This means that there is an influence of aquatic water games on critical thinking skills in children aged 5-6 years